Reducing the Numerical Calculation in the Wave Iterative Method by Image Processing Techniques - Hrizi, H.; Sboui, N. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The wave iterative method is a numerical method used to model electromagnetic circuits. It is based on the concept of waves in the place of electromagnetic fields. To study the electronic circuits having complex structures, this method requires much time. We propose in this article to improve this method by using techniques of image processing. That’s why the structure of the studied circuit is considered as an image. The objective is to reduce computing time by reducing dimensions of the calculation matrices. The reduced matrices are built containing only the important part of the information. Our goal is to prove that the most important zones in the structure are located in the contour with small steps in the vicinity of the contour.